Fluktuasi dan Kelimpahan Fitoplankton di Danau Laguna Ternate Maluku Utara - Yuliana Yuliana; Thamrin Thamrin (Universitas Gadjah Mada, 2007)
The objective of this research was to know the fluctuation and abundance of phytoplankton at Laguna Lake, North Moluccas. This research was conducted for 3 periods, from June to July 2005. Sampling of plankton were taken biweekly in 4 stations and 3 depths (0, 5, and 10 m) by filtration method.The results showed that there were 9 genera from 3 classes: Bacillariophyceae (6 genera), Cyanophyceae (2 genera), and Dinophyceae (1 genera). Plankton abundance on period I ranged 1.14 x 104-3.49 x 104 ind/l, period II ranged 7.64 x 103 -4.73 x 104 ind/l, and period III ranged 9.29 x 103-3.78 x 104 ind/l, the highest on period II (3.19 x 105 ind/l) and the lowest on period I (2.49 x 105 ind/l). The phytoplankton abundance in each station were station 1 = 9.29 x 103-4.73 x 104 ind/l, station 2 = 1.51 x 104-4.52 x 104 ind/l, station 3 = 7.64 x 103-3.45 x 104 ind/l, and station 4 = 1.14 x 104-3.49 x 104 ind/l. The highest phytoplankton abundance was in station 2 (2.45 x 105 ind/l) and the lowest in station 4 (1.68 x 105 ind/l). Whereas, phytoplankton abundance based on depth were 0 m = 9,29 x 103-3,92 x 104 ind/l, 5 m = 7,64 x 103-4,73 x 104 ind/l, and 10 m = 1,18x 105-3,7 x 105 ind/l, the highest on 10 m (2.91 x 105 ind/l) and the lowest on 0 m (2.49 x105 ind/l). The range value of biological index such as diversity index (H’) on period I was 0,5276-1,1853, period II was 0,6138-1,1635, and persiod III was 0.6276-1.2264; equitability index (E) on period I was 0.4422-0.8550, period II was 0.4725-0.8393, and period III was 0.5674-0.8575; and dominant index (D) on period I was 0.3403-0.7032, period II was 0.3584-0.6597, and period III was 0.3195-0.6647.